Serious Adverse Events Reporting in Phase III Randomized Clinical Trials of Colorectal Cancer Treatments: A Systematic Analysis - Yao, Yanhong; Liu, Zhentao; Zhang, Hua; Li, Jian; Peng, Zhi; Yu, Jinyu; Cao, Baoshan; Shen, Lin (Frontiers in Pharmacology, 2021)
Objective: This article systematically reviewed the SAEs reports of randomized multicenter phase III clinical trials of colorectal cancer treatments and analyzed the influencing factors. Methods: We reviewed all articles about phase III randomized clinical trials of colorectal cancer treatments published in the PubMed, Embase, Medline, and New England Journal of Medicine databases from January 1, 1993, to December 31, 2018, and searched the registration information of clinical trials via the internet sites such as “clinicaltrials.gov” . We analyzed the correlation between the reported proportion (RP) of SAEs in the literature and nine elements, including the clinical trial sponsor and the publication time. Chi-square tests and binary logistic regression were used to identify the factors associated with improved SAEs reports. This study was registered on PROSPERO. Results: Of 1560 articles identified, 160 were eligible, with an RP of SAEs of 25.5%. In forty-one publications reporting SAEs, only 14.6% (6/41) described the pattern of SAEs in detail. In clinical trials sponsored by pharmaceutical companies, the RP of SAEs was significantly higher than that in those sponsored by investigators (57.6% versus 20.7%, p < 0.05). From 1993 to 2018, the RP of SAEs gradually increased (none (0/6) before 2000, 17.1% (12/70) from 2000 to 2009, and 34.5% (29/84) after 2009). The average RP of SAEs published in the New England Journal of Medicine (N Engl J Med), the Lancet, the Journal of the American Medical Association (JAMA), the Lancet Oncology (Lancet Oncol), and the Journal of Clinical Oncology (J Clin Oncol) was significantly higher than that published in other journals (31.9% versus 16.7%, p = 0.030). In the clinical trials referenced by clinical guidelines, the RP of SAEs was higher than the others (32.0% versus 15.9%, p = 0.023). Logistic regression analysis showed that pharmaceutical company sponsorship, new drug research, and sample size greater than 1000 were positive influencing factors for SAEs reporting. Conclusion: Although the RP of SAEs increased over time, SAEs reporting in clinical trials needs to be further improved. The performance, outcomes and prognosis of SAEs should be reported in detail to guide clinical practice in the real world.